The experimental and numerical investigation on the enhancement of stagnation and parallel zones of laminar jet. (1st October 2020) - Barik, K.; Swain, B.; Behera, A.; Chitransh, S.; Mohapatra, S.S.
Highlights: Decrement in surface tension leads to enhancement in heat transfer. Numerical analysis shows close agreement with the current experimental results. Heat flux achieved in case of CTAB (240 ppm) is 1.35 times higher than pure water. Abstract: The effectiveness of a laminar jet in various applications depends on the hydraulic jump and stagnation zone lengths. After impingement, the early occurrence of the above stated two parameters declines the effectiveness of the laminar water jet. In the absence of mechanical modification, the enhancement in hydraulic jump and stagnation zone lengths has been a challenging task for the recent generation researchers. Therefore, in the current work, an attempt has been made to achieve the above mentioned by chemical modification process which includes the thermo-physical property modification of fluid in the favorable direction. The hydrodynamics study clearly indicate that the reduction in viscosity and surface tension of the coolant step up hydraulic jump and stagnation zone lengths and the heat transfer analysis reveals that the augmentation is achieved due to the alteration of the aforesaid properties. It is observed that the role of surface tension and viscosity in the variation of hydraulic jump lengths and stagnation jump lengths remains unaltered. However, the intensity of alteration decreases. The experimental result obtained from the hydrodynamics investigation is compared with the results obtained from CFD simulation. The comparison illustrates that the experimental data have been in good agreement with the results predicted by CFD models and information reported by the previous researchers.